Knowledge, Perception, and Reporting Practices of Healthcare Providers about Adverse Events Following the COVID-19 Vaccination in Iraq(Conference Paper )# - Basma Zuheir Al-Metwali; Farah Hatem Nsaif (College of Pharmacy University of Baghdad, 2023)
Routine vaccination activities, such as detection, reporting, and management of adverse events following immunization (AEFIs), are generally handled by healthcare providers (HCPs). Safe vaccines against severe acute respiratory syndrome coronavirus (SARS-CoV-2) were introduced to control the Coronavirus Disease-19 (COVID-19) pandemic. The study aimed to assess the knowledge, perceptions, and practice of HCPs in Iraq about reporting adverse events following COVID-19 vaccination, and their association with sociodemographic variables. The study was a cross-sectional study that was carried out between August and September 2021 at the COVID-19 vaccination centers in Iraq. This study used an online and paper-based questionnaire, which was distributed among HCPs (physicians and pharmacists) in COVID-19 vaccination centers. A total of 117 pharmacists and physicians responded to the survey. Two-thirds of respondents were pharmacists. The majority of the respondents (49.6%) had fair knowledge levels on AEFIs. The perception of 43% of the participants was very good, whereas the perception of 28%, 23%, and 6% of the participants was fair, good, and poor, respectively. The reporting practice of HCPs was inadequate in 53% of respondents. The number of pharmacists who had good knowledge of AEFIs was significantly higher than that of the physicians. The age group (30-39) years of HCPs was significantly associated with more positive perception towards AEFIs. The number of pharmacists that had good perception was significantly higher than that of the physicians. Furthermore, HCPs aged 30 to 39 years had significantly higher reporting practices than other age groups. The study highlighted that the HCPs working at the COVID-19 vaccination centers have low knowledge of AEFIs. On the other hand, HCPs had more positive perception towards reporting AEFIs. Education programs and reference materials are needed to increase their awareness about AEFIs.